THE ROLE OF ATMOSPHERE STORE AND HEDONIC SHOPPING MOTIVATION IN IMPULSIVE BUYING BEHAVIOR - Dikdik Harjadi; Iqbal Arraniri; Dewi Fatmasari (Jurnal Riset Bisnis dan Manajemen, 2021)
The purpose of this study would be to see how certain variables, such as Store Atmosphere and Hedonic Shopping Motivation, influenced impulse purchases. There are some linear regression models used. The authentication function’s goal is to determine the validity of such a hypothesis, which also is achieved by collecting data from its surrounding region. The purposive method is a strategy that is related to specific criteria, and the sample throughout this study was made up of buyers from modern retail outlets within Kuningan Regency. There were just as many about 96 people who took part in the study. The amount was rounded towards 100 participants to make work successful. The environment of modern major retailers and hedonic shopping motivation does have a positive impact on impulse buying.